Nurses' Perception of Organisational Justice and its Effect on Bullying Behaviour in the Hospitals of Turkey - Hanım Seyrek; Dilek Ekici (Baqiyatallah University of Medical Sciences, 2017)
Background: The 'Organizational Justice' concept is used in order to determine whether the administrator is fair to his personnel or not. It is said that those who get bullied are usually terrorized, annoyed, excluded, belittled, deprived of resources, isolated and prevented from claiming rights. Objective: The purpose of this study is to determine nurses' perception of organizational justice and its effect on the bullying behaviour they are exposed to. Methods: The cross-sectional study was conducted on nurses at a university hospital and a private hospital in Ankara. In this regard, 250 nurses who had been serving in their respective hospitals for 6 months participated in the study. The variables were measured under 2 categories: bullying and perception of organizational justice. A simple regression analysis was carried out in order to determine the bullying behaviour which causes the nurses' justice perceptions. Results: According to the survey, the nurses are most likely to perceive injustice in the area of distributional justice. Results revealed that the ratio of nurses who were exposed to bullying in the workplace was 28%. There was a significant and negative relation between the nurses' distributional justice perception and the bullying they were exposed to. Conclusion: The employees whose organizational justice perceptions are low, display a threatening and negative behaviour towards their colleagues and the institution. They feel themselves to be threatened when they think that they can't communicate with upper management respectfully and also when they believe that their managers are unjust in performance assessment, in assessing salaries and promotion.